Buku Ajar Fisika Materi Suhu dan Kalor Kelas XI dengan Pendekatan Pembelajaran Terintegrasi Ayat Al- Qur’an dan Al- Hadits - Fikri, Muhammad; Al Mubarokah, Nurul Hidayah (CV. Media Digital Publikasi Indonesia, 2023)
The problem encountered at MA Nurul Hidaya Assonhaji is that physics is a very difficult subject and students do not like. The teaching materials/ worksheets used from several publishers are usually purchased/ photocopied which in general are not in accordance with the needs of students and teachers in schools so that teachers use textbooks. Therefore, the researchers developed a Physics Textbook for Class XI Materials of Temperature and Heat with an Integrated Generative Learning Approach Al - Qur'an and Hadith verses that are in accordance with the characteristics and needs of students so that students can study independently and prefer physics lessons. This research is a development research. This researcher consisted of 4 stages, namely: defining, designing, developing, data collection instruments used were textbook validation sheets, student response questionnaires. The textbook validation test was assisted by 2 validator lecturers. After the textbook feasibility test, a student response questionnaire was distributed involving 25 students. Filling out the questionnaire using a Liketk scale with a count of 1-4, the data can be analyzed quantitatively in accordance with the criteria of validity and practicality. From the results of the study, it was shown that the Material Physics Textbook for Class XI with an Integrated Generative Learning Approach Al-Qur'an and Hadith verses was quite valid with the validity result obtained was 60%. Then the Physics Textbook for Class XI Materials of Temperature and Heat With an Integrated Generative Learning Approach The verses of the Qur'an and Hadith are quite practical to use after a limited trial of 25 students with an average result of 80%.